Agro-technology Transfer through tribal sub-plan - Bandyopadhyay, S.; Ray, P.; Padua, S.; Jena, R. K.; Sah, K. D.; Baruah, U.; Singh, S. K.; Ray, S. K. (Indian Farming, 2016)
Land suitability based crop planning approach is an efficient means of agro-technology transfer among the tribal farmers in the north eastern region. Such approach of crop planning is of utmost importance for sustainable agricultural development in this region. The Tribal Sub-Plan has opened a new vista in disseminating and implementing modern technologies and research output among the tribal population of the country. The TSP has been an impetus for the tribal population to make agriculture a profitable venture beyond the subsistence level. Besides, the scheme has encouraged the tribal farmers for crop diversification during rabi season. Under the umbrella of TSP, continuous dissemination of the new technologies among the tribal population is essential to enhance their livelihood security in particular and the region as a whole.